An Extensive Analysis Of Randomized Controlled Trials Contrasting Computed Tomography-Guided Lung Biopsies Performed At Low Versus Standard Dosages - Anton; Yusuf (The International Journal of Medical Science and Health Research, 2024)
Background: Low-Dose CT (LDCT) protocol lowers radiation dose without compromising image quality, reducing health risks. Randomized Controlled Trials have shown promising results, but further research is needed. Methods: The study followed PRISMA 2020 standards to compare LDCT-guided and SDCT-guided lung biopsies using various CT scanners. The authors meticulously searched databases and reference lists to identify relevant articles and ensure accuracy and dependability of the findings. Result: Following a thorough three-level screening process, six publications were determined to be directly related to our ongoing systematic examination. After that, the entire text was thoroughly examined, and these articles were examined even more closely. Conclusion: The study investigates radiation dose in CT scans, focusing on minimizing unnecessary exposure. Some strategies are to use iterative algorithms and reduce the tube voltage, current, and scanning time. LDCT protocols were linked to lower radiation doses, but inconsistencies in assessing image quality across studies prevent a meta-analysis.